Features of simple inflammation markers in assessing the plaque vulnerability in patients with acute coronary syndrome - A. N. Kovalskaya; G. R. Bikbaeva; D. V. Duplyakov; E. V. Savinova (Российский кардиологический журнал)
Aim. To assess the relationship between simple inflammation markers and plaque vulnerability criteria according to coronary computed tomography angiography (CCTA), as well as lipid profile parameters in patients with acute coronary syndrome (ACS).Material and methods. This prospective, randomized, single-center study included 125 patients admitted urgently with the clinical performance of ACS (myocardial infarction (MI) — 94 patients; unstable angina (UA) — 31). All patients underwent percutaneous coronary intervention of the infarct-related artery. In addition, all patients had atherosclerotic plaques with stenosis <50% in one or two non-infarct-related arteries. Treatment of ACS was carried out according to the guidelines. One month after ACS, all patients underwent CCTA to detect vulnerable plaques, as well as lipid profile analysis (total cholesterol (TC), lowdensity lipoprotein (LDL) cholesterol, triglycerides, high-density lipoprotein (HDL) cholesterol), simple inflammatory biomarkers C-reactive protein (CRP), neutrophilto-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-HDL-C ratio (MHR), lymphocyte-to-monocyte ratio (LMR), lymphocyte-to-CRP ratio (LCR).Results. Of the 125 patients included in the study, MI was diagnosed in 94 (75%) patients, and UA in the remaining cases. In the acute period, in patients with MI, the HDL-C value was significantly lower 1,2 (1,03; 1,5) mmol/L than in the group of patients with UA (1,4 (1,24; 1,58) mmol/L), p=0,044. NLR was higher in patients with MI — 2,96 (2,09; 3,99) versus 2,21 (1,69; 2,71) in the UA group (p=0,018). One month after the index event, the HDL-C level remained significantly lower in the MI group 1,08 (0,95; 1,34) mmol/L, and the MHR was higher (0,52 (0,37; 0,64)) than in UA (1,25 (1,15; 1,34) mmol/L and 0,41 (0,31; 0,52)), respectively. The LCR after 1 month was almost 2 times higher in the UA group — 1,32 (0,65; 2,28) versus 0,66 (0,34; 1,28) in the MI group (p=0,028). The vulnerability criteria of plaques according to CCTA data were identified in 55 (44%) patients in the general group with ACS, of which positive remodeling was detected in 35 patients, a low-density area — in 30, and punctate calcifications (PC) — in 11. Patients in the general ACS group were divided by vulnerability criteria. Patients with PC had a significantly (p=0,004) higher level of HDL-C 1,22 (1,02; 1,34), compared to those without it 0,97 (0,77; 1,13). The MHR was higher (p=0,024) in the presence of PC (0,61 (0,48; 0,86)) than without it (0,46 (0,35; 0,63)). No significant differences were found for other indicators. When conducting the ROC analysis in patients with PC, the threshold level of HDL-C was 0,98 (AUC: 0,76, Sensitivity 66,7%, Specificity 77,4%), the threshold level of HDL-C in the presence of low-density area simultaneously with PC was also 0,98 (AUC: 0,83, Sensitivity 75%, Specificity 75,7%).Conclusion. The HDL-C and MHR indicators significantly changed in patients who had ACS and microcalcifications in the plaques.